Spring frost frequency increased in North America but decreased in Eurasia from 1948 to 2016 - Wei Guo; Chuhan Lu; Ping Xia; Lijiang Fu; Govindjee Govindjee; Hao Tang; Jian Chen; Li Song; Jinglu Tan; Zhenyu Xu; Ya Guo (Theoretical and Applied Climatology, 2026)

Bicarbonate is a key regulator but not a substrate for O2 evolution in Photosystem II - David J. Vinyard; Govindjee Govindjee (Photosynthesis Research, 2024)
Photosystem II (PSII) uses light energy to oxidize water and to reduce plastoquinone in the photosynthetic electron transport chain. O 2 is produced as a byproduct. While most members of the PSII research community agree that O 2 originates from water molecules, alternative hypotheses involving bicarbonate persist in the literature. In this perspective, we provide an overview of the important roles of bicarbonate in regulating PSII activity and assembly. Further, we emphasize that biochemistry, spectroscopy, and structural biology experiments have all failed to detect bicarbonate near the active site of O 2 evolution. While thermodynamic arguments for oxygen-centered bicarbonate oxidation are valid, the claim that bicarbonate is a substrate for photosynthetic O 2 evolution is challenged.

From leaf to multiscale models of photosynthesis: applications and challenges for crop improvement - Alexandrina Stirbet; Ya Guo; Dušan Lazár; Govindjee Govindjee (Photosynthesis Research, 2024)

Remembering Jan Amesz (1934–2001): a great gentleman, a major discoverer, and an internationally renowned biophysicist of both oxygenic and anoxygenic photosynthesisa - Govindjee Govindjee; Bas Amesz; Győző Garab; Alexandrina Stirbet (Photosynthesis Research, 2024)

On the Pelletier and Caventou (1817, 1818) papers on chlorophyll and beyond - Govindjee Govindjee; Alexandrina Stirbet; Jonathan S. Lindsey; Hugo Scheer (Photosynthesis Research, 2024)

Reduced expression of chlorophyllide a oxygenase (CAO) decreases the metabolic flux for chlorophyll synthesis and downregulates photosynthesis in tobacco plants - Ajaya K. Biswal; Gopal K. Pattanayak; Kamal Ruhil; Deepika Kandoi; Sushree S. Mohanty; Sadhu Leelavati; Vanga S. Reddy; Govindjee Govindjee; Baishnab C. Tripathy (Physiology and Molecular Biology of Plants, 2024)

Paul A. Castelfranco (1921–2021): a scientist par excellence, a man of lasting faith, and ever a humanist - R. W. Breidenbach; Ann M. Castelfranco; John Castelfranco; Govindjee Govindjee; Kevin M. Smith; Alan Stemler (Photosynthesis Research, 2023)

Solar energy conversion by photosystem II: principles and structures - Dmitry Shevela; Jan F. Kern; Govindjee Govindjee; Johannes Messinger (Photosynthesis Research, 2023)
Photosynthetic water oxidation by Photosystem II (PSII) is a fascinating process because it sustains life on Earth and serves as a blue print for scalable synthetic catalysts required for renewable energy applications. The biophysical, computational, and structural description of this process, which started more than 50 years ago, has made tremendous progress over the past two decades, with its high-resolution crystal structures being available not only of the dark-stable state of PSII, but of all the semi-stable reaction intermediates and even some transient states. Here, we summarize the current knowledge on PSII with emphasis on the basic principles that govern the conversion of light energy to chemical energy in PSII, as well as on the illustration of the molecular structures that enable these reactions. The important remaining questions regarding the mechanism of biological water oxidation are highlighted, and one possible pathway for this fundamental reaction is described at a molecular level.

David (Dave) Charles Fork (1929–2020): a gentle human being, a great experimenter, and a passionate researcher - Govindjee Govindjee; Laurie Fork Peterson; Kazuhiko Satoh; Stephen Herbert; Yaroslav de Kouchkovsky; Ulrich Schreiber; Norio Murata; Gunnar Öquist; Anthony W. D. Larkum; Tetsuo Hiyama; Joseph A. Berry (Photosynthesis Research, 2023)

In memory of Vladimir Anatolievich Shuvalov (1943–2022): an outstanding biophysicist - Lyudmila G. Vasilieva; Olga P. Kaminskaya; Andrei G. Yakovlev; Anatoliy Ya. Shkuropatov; Alexey Yu. Semenov; Victor A. Nadtochenko; Alexander A. Krasnovsky; William W. Parson; Suleyman I. Allakhverdiev; Govindjee Govindjee (Photosynthesis Research, 2022)

Remembering Robert (Bob) Togasaki (1932–2019): A leader in Chlamydomonas genetics and in plant biology, as well as a teacher par excellence - Susan J. Carlson; Carl E. Bauer; Govindjee Govindjee (Photosynthesis Research, 2022)

Natural variation in the fast phase of chlorophyll a fluorescence induction curve (OJIP) in a global rice minicore panel - Naveed Khan; Jemaa Essemine; Saber Hamdani; Mingnan Qu; Ming-Ju Amy Lyu; Shahnaz Perveen; Alexandrina Stirbet; Govindjee Govindjee; Xin-Guang Zhu (Photosynthesis Research, 2021)

Three overlooked photosynthesis papers of Otto Warburg (1883–1970), published in the 1940s in German and in Russian, on light-driven water oxidation coupled to benzoquinone reduction - Holger Dau; Boris Ivanov; Dmitry Shevela; William H. Armstrong; Govindjee Govindjee (Photosynthesis Research, 2021)

Martin David Kamen (1913–2002): discoverer of carbon 14, and of new cytochromes in photosynthetic bacteria - Govindjee Govindjee; Robert E. Blankenship (Photosynthesis Research, 2021)

A tribute - Govindjee Govindjee; Brij Sawhney; Autar Mattoo (Plant Physiology Reports, 2021)

Honoring Bacon Ke at 100: a legend among the many luminaries and a highly collaborative scientist in photosynthesis research - Govindjee Govindjee; Yun-Kang Shen; Xin-Guang Zhu; Hualing Mi; Teruo Ogawa (Photosynthesis Research, 2021)

Ramesh Chandra Sinha (1934–2020) - Govindjee Govindjee; D. Venkata Raghava Reddy (Archives of Virology, 2021)

Development of a minimized model structure and a feedback control framework for regulating photosynthetic activities - Lijiang Fu; Govindjee Govindjee; Jinglu Tan; Ya Guo (Photosynthesis Research, 2020)

International conference on “Photosynthesis and Hydrogen Energy Research for Sustainability-2019”: in honor of Tingyun Kuang, Anthony Larkum, Cesare Marchetti, and Kimiyuki Satoh - Maria M. Borisova-Mubarakshina; Anatoly A. Tsygankov; Tatsuya Tomo; Suleyman I. Allakhverdiev; Julian J. Eaton-Rye; Govindjee Govindjee (Photosynthesis Research, 2020)

Unique features of the ‘photo-energetics’ of purple bacteria: a critical survey by the late Aleksandr Yuryevich Borisov (1930–2019) - Govindjee; Andrei P. Razjivin; Vladimir S. Kozlovsky (Photosynthesis Research, 2020)

Tribute: a salute to Alexander Yurievich Borisov (1930–2019), an outstanding biophysicist - Alexey Yu. Semenov; Elena A. Kotova; Andrei P. Razjivin; Govindjee (Photosynthesis Research, 2020)

A tribute to Maarib (Darwish Lutfi Bakri) Bazzaz (1940–2020): the one who proved the existence of “new” chlorophylls in plants - Govindjee Govindjee; Barbara A. Zilinskas; Richard G. Brereton; Rita Khanna; Rajni Govindjee (Plant Physiology Reports, 2020)

From δ-aminolevulinic acid to chlorophylls and every step in between: in memory of Constantin (Tino) A. Rebeiz, 1936–2019 - Govindjee Govindjee; Donald P. Briskin; Christoph Benning; Henry Daniell; Vladimir Kolossov; Hugo Scheer; Mark Rebeiz (Photosynthesis Research, 2020)
Constantin A. (Tino) Rebeiz, a pioneer in the field of chlorophyll biosynthesis, and a longtime member of the University of Illinois community of plant biologists, passed away on July 25, 2019. He came to the USA at a time that was difficult for members of minority groups to be in academia. However, his passion for the complexity of the biochemical origin of chlorophylls drove a career in basic sciences which extended into applied areas of environmentally friendly pesticides and treatment for skin cancer. He was a philanthropist; in retirement, he founded the Rebeiz Foundation for Basic Research which recognized excellence and lifetime achievements of selected top scientists in the general area of photosynthesis research. His life history, scientific breakthroughs, and community service hold important lessons for the field.

Christiaan Sybesma (August 31, 1928–January 31, 2018), an extraordinary biophysicist of our time - Wim J. Vredenberg; Govindjee Govindjee (Photosynthesis Research, 2020)
We provide here a brief Tribute to Christiaan Sybesma (1928–2018), a highly respected biophysicist of our time. We remember him by giving a brief highlight of his life and a glimpse of his outstanding contributions in photosynthesis. He was a charming and highly respected scientist of our time.

Satish Chandra Maheshwari (1933–2019)—a brilliant, passionate and an outstanding shining light for all of plant biology - Ashwani Pareek; Vineet Soni; Sudhir K. Sopory; Jitendra P. Khurana; K. Sowjanya Sree; Akhilesh K. Tyagi; Sushila Narsimhan; Govindjee Govindjee (Physiology and Molecular Biology of Plants, 2020)

Remembering Melvin Calvin (1911–1997), a highly versatile scientist of the 20th century - Govindjee Govindjee; Arthur Nonomura; Hartmut K. Lichtenthaler (Photosynthesis Research, 2020)

CO2 uptake and chlorophyll a fluorescence of Suaeda fruticosa grown under diurnal rhythm and after transfer to continuous dark - Silas Wungrampha; Rohit Joshi; Ray S. Rathore; Sneh L. Singla-Pareek; Govindjee; Ashwani Pareek (Photosynthesis Research, 2019)

Eugene I. Rabinowitch: A prophet of photosynthesis and of peace in the world - Govindjee; George C. Papageorgiou; Rajni Govindjee (Photosynthesis Research, 2019)

Thomas John Wydrzynski (8 July 1947–16 March 2018) - Brendon Conlan; Govindjee; Johannes Messinger (Photosynthesis Research, 2019)

Changes in the photosynthesis properties and photoprotection capacity in rice (Oryza sativa) grown under red, blue, or white light - Saber Hamdani; Naveed Khan; Shahnaz Perveen; Mingnan Qu; Jianjun Jiang; Govindjee; Xin-Guang Zhu (Photosynthesis Research, 2019)

A sixty-year tryst with photosynthesis and related processes: an informal personal perspective - Govindjee (Photosynthesis Research, 2019)

Low temperature induced modulation of photosynthetic induction in non-acclimated and cold-acclimated Arabidopsis thaliana: chlorophyll a fluorescence and gas-exchange measurements - Kumud B. Mishra; Anamika Mishra; Jiří Kubásek; Otmar Urban; Arnd G. Heyer; Govindjee (Photosynthesis Research, 2019)

Honoring eight senior distinguished plant biologists from India - Rajagopal Subramanyam; Suleyman I. Allakhverdiev; Govindjee (Photosynthesis Research, 2019)

In memory of Thomas Turpin Bannister (1930–2018) - Edward Laws; Alan Weidemann; George Hoch; Horatio Bannister; Robert S. Knox; Govindjee (Photosynthesis Research, 2018)

Remembering Otto Kandler (1920–2017) and his contributions - Govindjee; Widmar Tanner (Photosynthesis Research, 2018)

Shmuel Malkin (1934–2017) - Stephen K. Herbert; Yona Siderer; Govindjee (Photosynthesis Research, 2018)

Gordon Research Conference on photosynthesis: photosynthetic plasticity from the environment to synthetic systems - Christopher Gisriel; Shai Saroussi; Silvia Ramundo; Petra Fromme; Govindjee (Photosynthesis Research, 2018)

On the origin of the slow M–T chlorophyll a fluorescence decline in cyanobacteria: interplay of short-term light-responses - Gábor Bernát; Gábor Steinbach; Radek Kaňa; Govindjee; Amarendra N. Misra; Ondřej Prašil (Photosynthesis Research, 2018)

Vyacheslav (Slava) Klimov (1945–2017): A scientist par excellence, a great human being, a friend, and a Renaissance man - Suleyman I. Allakhverdiev; Sergey K. Zharmukhamedov; Margarita V. Rodionova; Vladimir A. Shuvalov; Charles Dismukes; Jian-Ren Shen; James Barber; Göran Samuelsson; Govindjee (Photosynthesis Research, 2018)

The paths of Andrew A. Benson: a radio-autobiography - Arthur M. Nonomura; Barry Holtz; Karl Y. Biel; Robert Cooney; George Lorimer; Govindjee (Photosynthesis Research, 2017)

Paul Henry Latimer (1925–2011): discoverer of selective scattering in photosynthetic systems - Margaret Gwyn Latimer; Thomas T. Bannister; Govindjee (Photosynthesis Research, 2017)

Evolution of the Z-scheme of photosynthesis: a perspective - Govindjee; Dmitriy Shevela; Lars Olof Björn (Photosynthesis Research, 2017)

Frederick Yi-Tung Cho (1939–2011) - Govindjee; John C. Munday; George C. Papageorgiou (Photosynthesis Research, 2017)

André Tridon Jagendorf (1926–2017): a personal tribute - Govindjee (Photosynthesis Research, 2017)

Remembering Navasard V. Karapetyan (1936–2015) - Nadezhda P. Yurina; Vladimir O. Popov; Alexander A. Krasnovsky; Govindjee (Photosynthesis Research, 2017)

David W. Krogmann, 1931–2016 - Jerry J. Brand; Cheryl A. Kerfeld; William A. Cramer; Govindjee (Photosynthesis Research, 2017)

International conference on “Photosynthesis Research for Sustainability-2016” - Anatoly A. Tsygankov; Suleyman I. Allakhverdiev; Tatsuya Tomo; Govindjee (Photosynthesis Research, 2017)

Honoring Jean-David Rochaix - Govindjee; Kevin Redding (Photosynthesis Research, 2017)

Effects of exogenous β-carotene, a chemical scavenger of singlet oxygen, on the millisecond rise of chlorophyll a fluorescence of cyanobacterium Synechococcus sp. PCC 7942 - Kostas Stamatakis; George C. Papageorgiou; Govindjee (Photosynthesis Research, 2016)

The slow phase of chlorophyll a fluorescence induction in silico: Origin of the S–M fluorescence rise - Alexandrina Stirbet; Govindjee (Photosynthesis Research, 2016)

Towards efficient photosynthesis: overexpression of Zea mays phosphoenolpyruvate carboxylase in Arabidopsis thaliana - Deepika Kandoi; Sasmita Mohanty; Govindjee; Baishnab C. Tripathy (Photosynthesis Research, 2016)

International conference on “Photosynthesis research for sustainability-2015” in honor of George C. Papageorgiou”, September 21–26, 2015, Crete, Greece - Suleyman I. Allakhverdiev; Tatsuya Tomo; Kostas Stamatakis; Govindjee (Photosynthesis Research, 2016)

In photosynthesis, oxygen comes from water: from a 1787 book for women by Monsieur De Fourcroy - Pierre Joliot; Antony R. Crofts; Lars Olof Björn; Christine T. Yerkes; Govindjee (Photosynthesis Research, 2016)

René Marcelle (December 30, 1931–December 18, 2011), the first editor-in-chief of Photosynthesis Research - Govindjee; Dominique Marcelle (Photosynthesis Research, 2016)

Louis Nico Marie Duysens (March 15, 1921–September 8, 2015): a leading biophysicist of the 20th century - Govindjee; M. P. J. Pulles (Photosynthesis Research, 2016)

Jalal A. Aliyev (1928–2016): a great scientist, a great teacher and a great human being - Irada M. Huseynova; Suleyman I. Allakhverdiev; Govindjee (Photosynthesis Research, 2016)

Vallabhaneni Sita Rama Das, 1933–2010: teacher and mentor - Sailaja V. Elchuri; Govindjee (Photosynthesis Research, 2016)

Hartmut Lichtenthaler: an authority on chloroplast structure and isoprenoid biochemistry - Thomas D. Sharkey; Govindjee (Photosynthesis Research, 2016)

Remembering James Alan Bassham (1922–2012) - Govindjee; Helen Bassham; Susan Bassham (Photosynthesis Research, 2016)

Gordon research conference on the dynamics and regulation of photosynthesis: from the origin of bio-catalysis to innovative solar conversion - Govindjee; Arthur R. Grossman; Devaki Bhaya (Photosynthesis Research, 2016)

Andrew A. Benson: personal recollections - Arthur Nonomura; George Lorimer; Barry Holtz; Victor Vacquier; Karl Y. Biel; Govindjee (Photosynthesis Research, 2016)

Remembering Jeanette Snyder Brown (1925–2014) - Winslow R. Briggs; Govindjee (Photosynthesis Research, 2016)

The two last overviews by Colin Allen Wraight (1945–2014) on energy conversion in photosynthetic bacteria - Péter Maróti; Govindjee (Photosynthesis Research, 2016)

Colin A. Wraight, 1945–2014 - Govindjee; Roger C. Prince; Donald R. Ort (Photosynthesis Research, 2016)

The slow S to M rise of chlorophyll a fluorescence reflects transition from state 2 to state 1 in the green alga Chlamydomonas reinhardtii - Sireesha Kodru; Tirupathi Malavath; Elsinraju Devadasu; Sreedhar Nellaepalli; Alexandrina Stirbet; Rajagopal Subramanyam; Govindjee (Photosynthesis Research, 2015)

Primary electron transfer processes in photosynthetic reaction centers from oxygenic organisms - Mahir Mamedov; Govindjee; Victor Nadtochenko; Alexey Semenov (Photosynthesis Research, 2015)

Mitochondrial electron transport protects floating leaves of long leaf pondweed (Potamogeton nodosus Poir) against photoinhibition: comparison with submerged leaves - Nisha Shabnam; P. Sharmila; Anuradha Sharma; Reto J. Strasser; Govindjee; P. Pardha-Saradhi (Photosynthesis Research, 2015)

Matthias Rögner (ed): Biohydrogen - Govindjee (Photosynthesis Research, 2015)

Albert W. Frenkel (1919–2015): photosynthesis research pioneer, much-loved teacher, and scholar - Govindjee; Susanna Frenkel (Photosynthesis Research, 2015)

Andrew A. Benson, 1917–2015 - Hartmut K. Lichtenthaler; Bob B. Buchanan; Roland Douce; Govindjee (Photosynthesis Research, 2015)

Gordon research conference on photosynthesis: from evolution of fundamental mechanisms to radical re-engineering - Fabrice Rappaport; Alizée Malnoë; Govindjee (Photosynthesis Research, 2015)

International conference on “photosynthesis research for sustainability-2014: in honor of Vladimir A. Shuvalov”, held on June 2–7, 2014, in Pushchino, Russia - Suleyman I. Allakhverdiev; Tatsuya Tomo; Govindjee (Photosynthesis Research, 2014)

Prasanna K. Mohanty (1934–2013): a great photosynthetiker and a wonderful human being who touched the hearts of many - Swati Tiwari; Baishnab Charan Tripathy; Anjana Jajoo; Anath Bandhu Das; Norio Murata; Prafullachandra Vishnu Sane; Govindjee (Photosynthesis Research, 2014)

Alexander V. Ruban: The photosynthetic membrane: Molecular mechanisms and biophysics of light harvesting - Govindjee (Photosynthesis Research, 2014)

The controversy over the minimum quantum requirement for oxygen evolution - Jane F. Hill; Govindjee (Photosynthesis Research, 2014)

Stories and photographs of William A. Arnold (1904–2001), a pioneer of photosynthesis and a wonderful friend - Lucinda Choules; Govindjee (Photosynthesis Research, 2014)

Alexander Abramovich Krasnovsky (1913–1993): 100th birth anniversary in Moscow, Russia - N. V. Karapetyan; Govindjee (Photosynthesis Research, 2014)

Photosynthetic responses of sun- and shade-grown barley leaves to high light: is the lower PSII connectivity in shade leaves associated with protection against excess of light? - Marek Zivcak; Marian Brestic; Hazem M. Kalaji; Govindjee (Photosynthesis Research, 2014)

International conference on “Photosynthesis research for sustainability-2013: in honor of Jalal A. Aliyev”, held during June 5–9, 2013, Baku, Azerbaijan - Suleyman I. Allakhverdiev; Irada M. Huseynova; Govindjee (Photosynthesis Research, 2013)

An invitation to the 16th international congress on photosynthesis research in 2013: opportunities and challenges in the 21st century - Robert E. Blankenship; Judy Musick; Jason Cooley; Susan Dutcher; Govindjee (Photosynthesis Research, 2013)

Photosynthesis Web resources - Larry Orr; Govindjee (Photosynthesis Research, 2013)

Experimental in vivo measurements of light emission in plants: a perspective dedicated to David Walker - Hazem M. Kalaji; Vasilij Goltsev; Karolina Bosa; Suleyman I. Allakhverdiev; Reto J. Strasser; Govindjee (Photosynthesis Research, 2012)

Young research investigators honored at the 2012 Gordon Research Conference on photosynthesis - Gary F. Moore; Gennady M. Ananyev; Govindjee (Photosynthesis Research, 2012)

Chlorophyll a fluorescence induction: a personal perspective of the thermal phase, the J–I–P rise - Alexandrina Stirbet; Govindjee (Photosynthesis Research, 2012)

Berger C. Mayne (1920–2011): a friend and his contributions to photosynthesis research - Darrell Fleischman; Gerald E. Edwards; Govindjee; Leland Mayne; Vijai Tyagi; Karen Jacobsen-Mispagel (Photosynthesis Research, 2012)

William L. Ogren was honored with a Lifetime Achievement Award by the Rebeiz Foundation for Basic Research - Archie R. Portis; Govindjee (Photosynthesis Research, 2012)

International Conference on “Photosynthesis Research for Sustainability-2011”, July 24–30, 2011, Baku, Azerbaijan - Suleyman I. Allakhverdiev; Irada M. Huseynova; Govindjee (Photosynthesis Research, 2012)

Young research investigators honored at the 2011 Gordon research conference on photosynthesis: ambiance and a perspective - Govindjee; Gennady M. Ananyev; Sergei Savikhin (Photosynthesis Research, 2011)

A tribute to Thomas Roosevelt Punnett, Jr. (1926–2008) - William Hagar; Hope Punnett; Laura Punnett; Govindjee (Photosynthesis Research, 2011)

A tribute to Seymour Steven Brody: in memoriam (November 29, 1927 to May 25, 2010) - Rhoda Elison Hirsch; Marvin Rich; Govindjee (Photosynthesis Research, 2010)

Celebrating Andrew Alm Benson’s 93rd birthday - Govindjee (Photosynthesis Research, 2010)

Photosynthesis online - Larry Orr; Govindjee (Photosynthesis Research, 2010)

Picosecond spectroscopy of the isolated reaction centers from the photosystems of oxygenic photosynthesis—ten years (1987–1997) of fun - Govindjee; Michael Seibert (Photosynthesis Research, 2010)

Gernot Renger (ed): Primary processes of photosynthesis: principles and apparatus, parts 1 and 2 - Govindjee (Photosynthesis Research, 2010)

Special educational issue on ‘Basics and application of biophysical techniques in photosynthesis and related processes’—Part B - Johannes Messinger; A. Alia; Govindjee (Photosynthesis Research, 2009)

Young research investigators honored at the 2008 and 2009 Gordon research conferences on photosynthesis: ambiance and a personal perspective - Govindjee (Photosynthesis Research, 2009)

Special educational issue on ‘Basics and application of biophysical techniques in photosynthesis and related processes’ - Johannes Messinger; A. Alia; Govindjee (Photosynthesis Research, 2009)

A tribute to Achim Trebst, a friend - Govindjee (Photosynthesis Research, 2009)

List of biography and history published mostly in Photosynthesis Research, 1988–2008 - Govindjee (Photosynthesis Research, 2009)

A viewpoint: Why chlorophyll a? - Lars Olof Björn; George C. Papageorgiou; Robert E. Blankenship; Govindjee (Photosynthesis Research, 2009)

Martin Gibbs and the peaceful uses of nuclear radiation, 14C - Clanton C. Black; Govindjee (Photosynthesis Research, 2009)

D1-arginine257 mutants (R257E, K, and Q) of Chlamydomonas reinhardtii have a lowered QB redox potential: analysis of thermoluminescence and fluorescence measurements - Stuart Rose; Jun Minagawa; Manfredo Seufferheld; Sean Padden; Bengt Svensson; Derrick R. J. Kolling; Antony R. Crofts; Govindjee (Photosynthesis Research, 2008)

Recollections of Thomas John Wydrzynski - Govindjee (Photosynthesis Research, 2008)

Aquafluo 2007: chlorophyll fluorescence in aquatic sciences, an international conference held in Nové Hrady - Ondrej Prasil; David J. Suggett; John J. Cullen; Marcel Babin; Govindjee (Photosynthesis Research, 2007)

Photosynthesis and the Web: 2008 - Larry Orr; Govindjee (Photosynthesis Research, 2007)

The International Society of Photosynthesis Research (ISPR) and its associated International Congress on Photosynthesis (ICP): a pictorial report - Govindjee; Hyungshim Yoo (Photosynthesis Research, 2007)

A Tale of Naming a Photosynthetic Bacterium - Govindjee (Photosynthesis Research, 2007)

Four young research investigators were honored at the 2006 Gordon Research Conference on Photosynthesis - Govindjee; A. William Rutherford; R. David Britt (Photosynthesis Research, 2007)

Six young research investigators were honored at an international conference in Russia - Govindjee; Alison Telfer (Photosynthesis Research, 2007)

Paul R. Gorham (April 16, 1918––November 9, 2006) - Constance G. Nozzolillo; Harriet Gorham; Govindjee (Photosynthesis Research, 2007)

Advances in Photosynthesis and Respiration, Volume 24 (Photosystem I) and Volume 25 (Chlorophylls and Bacteriochlorophylls) - Govindjee (Photosynthesis Research, 2007)

Thirty Years of Photosynthesis 1974–2004, by Grahame J. Kelly and Erwin Latzko - Archie R. Portis; Govindjee (Photosynthesis Research, 2006)

Advances in Photosynthesis and Respiration, Volume 23: Structure and Function of Plastids - Govindjee (Photosynthesis Research, 2006)

International Photosynthesis Congresses (1968–2007) - Govindjee; David Knaff (Photosynthesis Research, 2006)

Photoprotection, Photoinhibition, Gene Regulation, and Environment, Volume 21, Advances in Photosynthesis and Respiration, Springer, Dordrecht - Govindjee (Photosynthesis Research, 2006)

Photosystem II: The Light-Driven Water: Plastoquinone Oxidoreductase, edited by Thomas J. Wydrzynski and Kimiyuki Satoh, Volume 22, Advances in Photosynthesis and Respiration, Springer, Dordrecht, The Netherlands - Govindjee (Photosynthesis Research, 2006)

The two Letters to the editors by Steve Vik and Wolfgang Junge - Govindjee (Photosynthesis Research, 2006)

Discoveries in Photosynthesis, Volume 20, Advances in Photosynthesis and Respiration - Govindjee (Photosynthesis Research, 2006)

Celebrating 20 years of historical papers in Photosynthesis Research★ - Govindjee (Photosynthesis Research, 2006)

Book review - Govindjee (Photosynthesis Research, 2006)

Chlorophyll a fluorescence induction kinetics in leaves predicted from a model describing each discrete step of excitation energy and electron transfer associated with Photosystem II - Xin-Guang Zhu; Govindjee; Neil R. Baker; Eric deSturler; Donald R. Ort; Stephen P. Long (Planta, 2005)

Advances in Photosynthesis and Respiration: Focus on Plant Respiration - Govindjee (Photosynthesis Research, 2005)

Book review: Molecular to Global Photosynthesis. Edited by Mary D. Archer and James Barber. Imperial College Press, London, UK, 2004, 764 pp (hardcopy, USD 158). - Govindjee; Christine H. Foyer (Photosynthesis Research, 2005)

A List of Photosynthesis Conferences and of Edited Books in Photosynthesis - Govindjee (Photosynthesis Research, 2004)

Celebrating the Millennium: Historical Highlights of Photosynthesis Research, Part 3 - Govindjee; John F. Allen; J. Thomas Beatty (Photosynthesis Research, 2004)

Discoveries in Oxygenic Photosynthesis (1727–2003): A Perspective - Govindjee; David Krogmann (Photosynthesis Research, 2004)

Celebrating the millennium – historical highlights of photosynthesis research, Part 2 - Govindjee; J. Thomas Beatty; Howard Gest (Photosynthesis Research, 2003)

A list of personal perspectives with selected quotations, along with lists of tributes, historical notes, Nobel and Kettering awards related to photosynthesis - Govindjee; David W. Krogmann (Photosynthesis Research, 2002)

Photosynthesis and the Web: 2001 - Larry Orr; Govindjee (Photosynthesis Research, 2001)

Light-induced and osmotically-induced changes in chlorophyll a fluorescence in two Synechocystis sp. PCC 6803 strains that differ in membrane lipid unsaturation - George C. Papageorgiou; Govindjee; Rajni Govindjee; Mamuro Mimuro; Kostas Stamatakis; Aikaterini Alygizaki-Zorba; Norio Murata (Photosynthesis Research, 1999)

On the requirement of minimum number of four versus eight quanta of light for the evolution of one molecule of oxygen in photosynthesis: A historical note - Govindjee (Photosynthesis Research, 1999)

A knowledge-based three dimensional model of the Photosystem II reaction center of Chlamydomonas reinhardtii - Jin Xiong; Shankar Subramaniam; Govindjee (Photosynthesis Research, 1998)

Mutagenesis of the D-E loop of photosystem II reaction centre protein D1. Function and assembly of photosystem II - Paula Mulo; Taina Tyystjärvi; Esa Tyystjärvi; # Govindjee; Pirkko Mäenpää; Eva-Mari Aro (Plant Molecular Biology, 1997)

Kinetics of the oxygen evolution step in plants determined from flash-induced chlorophyll t a fluorescence - Vladimir P. Shinkarev; Chunhe Xu; Govindjee; Colin A. Wraight (Photosynthesis Research, 1997)